Budaya Kerja Polri dalam Sistem Pelayanan Masyarakat di Polres Bengkulu Tengah - Henny Aprianty; Saikal Mulyadi; Rahiman Dani; Heru Purnawan (Universitas Medan Area, 2023)
This article aims to discuss police services which ideally must work in a systematic, orderly, and controlled manner based on predetermined rules, which in reality have not been fully implemented. However, there are still complaints about the state of service to the community managed by the state apparatus, namely (POLRI), so it is necessary to increase service discipline and productivity by introducing a culture with work cultural values that are in harmony with national morals, values, and culture. The focus of the main discussion that will be put forward and explored in this work concerns the work culture of the police in the Central Bengkulu Police community service system. The purpose of this is to analyze the work culture of the police within the police staffing system in Central Bengkulu. The research in this work uses descriptive and qualitative methods; The material for this research comes from primary data and secondary data. Documentation, observation, and interviews are used as techniques in data collection. Data analysis with qualitative methods is presented descriptively. The results of this study indicate that: The work culture of the Police in the Bengkulu Police community service system has been carried out appropriately and responsibly following the work culture, regulations, and values. Officers also meet the requirements and are responsible for implementing a police work culture in the Central Bengkulu Police social service system. The expected implication of this study is that with a work culture that is in harmony with regional culture and the basis of the state, the apparatus can carry out work activities to the maximum and wholeheartedly in the Central Bengkulu region.